Implementation of Body-Movement Method in Teaching Basic Vocabulary at University Muhammadiyah of Enrekang - jabri, Umiyati; Samad, Ita Sarmita; Nurazikin, Nurazikin (Maspul Journal of English Studies, 2022)
The subject of this research was vocabulary class in the Muhammadiyah University of Enrekang, 2021/2022 academic year. The data were in the form of quantitative data. The quantitative data were collected from the students’ vocabulary score of pre-test and post-test to see the improvement of the students’ vocabulary mastery. The research findings showed that vocabulary mastery of most students’ increase after body movement game technique was used in the teaching and learning process. It was indicated by the increase of the mean students’ vocabulary score in the pre-test and post-test (52, 07 to 76, 57). The students’ involvement and classroom interaction during the implantation of the game were increased. It was showed by students’ enthusiasm during the game. They tried to be the first winner and raised their competitiveness among them. In addition, the implementation of Body Movement Game technique and the complementary actions were successful to help the students’ memorize and understand new words easily. In conclusion, the students’ vocabulary mastery was increased through the implementation of Body Movement Game.